Development of Formulae to Determine Living Stature using Handprint Anthropometry of Tagalog People in the Philippines - Moorthy, Tharmar Nataraja; Dinglasa, Ivan Nikkimor Lao; Artaria, Myrtati Dyah (Folia Medica Indonesiana, 2023)
Highlights: 1. This is the first-ever anthropological study on Tagalog people in the Philippines that has established formulae for determining stature using handprint length measurements. 2. This study has generated formulae that are applicable for personal identification purposes within real crime scenes. Abstract Forensic science plays a crucial role in the pursuit of justice, particularly through the identification of physical evidence found at crime scenes, such as human fingerprints and handprints. This study aimed to develop formulae for determining living stature using the handprint anthropometry of Tagalog people, an indigenous ethnic group in the Philippines. A total of 360 Tagalog volunteers, comprising 180 men and 180 women, were recruited. This study excluded subjects who had finger and hand-related diseases, injuries, or were under the age of 18. The materials used were a stadiometer for height measurement, a digital vernier caliper for handprint measurements, and a handprint kit to collect handprints. Five length measurements were collected for each handprint. The length measurement spanned the distance from the middle wrist crease to the tips of each of the five fingers. The data were analyzed statistically using regression analysis (p<0.05) in IBM SPSS Statistics for Windows, version 26.0 (IBM Corp., Armonk, N.Y., USA). The analysis results produced equations for determining stature using all the length measurements of the handprints. The study involved the calculation of correlation coefficients (r values) and standard deviations using the stature and handprint lengths of individuals of both genders. The results are presented in the form of tables and figures. The study concluded with the development of regression equations that may be utilized for determining stature based on various handprint length measurements of the Tagalog people. This study represents the first-ever anthropological study conducted on the Philippine Tagalog population within the scope of this research subject matter. The formulae can be applied to actual crime scenes for the purpose of personal identification.